Pancasila sebagai Dasar Nkri - Kayla Nazwa Sabilla; Muhammad Ibnu Ismail Lubis (International Forum of Researchers and Lecturers, 2025)
Pancasila is the state ideology that is the main foundation in the life of the nation and state in Indonesia. As the nation's ideology, Pancasila contains noble values ​​that reflect the diversity of culture, religion, and traditions of Indonesian society. This study aims to analyze the role of Pancasila as the basis of the Unitary State of the Republic of Indonesia (NKRI) in maintaining unity, justice, and diversity amidst the challenges of globalization and socio-political dynamics. The method used is a literature review with a descriptive-analytical approach to explore the relevance of Pancasila in the current context. The results of the study show that Pancasila remains a solid guideline in facing various challenges, such as disintegration, radicalism, and identity crisis. Therefore, strengthening the understanding and implementation of Pancasila values ​​in everyday life is an urgency that must continue to be improved in order to maintain the integrity of the NKRI. This study recommends more intensive education and socialization efforts of Pancasila values ​​for the younger generation as the nation's successors.